Personnel profile - Alvin L. Throne - (:unkn) unknown (My University, 1969)
The UWM Field Stations Committee is composed of dedicated individuals interested in preserving natural areas for educational and scientific purposes. Success in the acquisition of such areas is often the result of the extra effort of one person. Such is the role played by Professor Alvin L. Throne, the Chairman of a previous committee and a former member of the present one. Until this Bulletin came into existence, there was no way to inform his many students and friends of his contributions, so this belated article is an expression of appreciation to Professor Throne for his years of dedicated service.
Keywords: Alvin Throne; UWM Field Station history